Suppressive effect of TNF-α and IL-1 on alveolar fibroblast proliferation in sarcoidosis - E. Fireman; D. Aderka; S. Ben Efraim; J. Greif; D. Wallach; M. Topilsky (Hindawi Limited, 1992)
The nature of soluble factors that regulate fibroblast proliferation have not been finally characterized. Our aim was to study the role of tumour necrosis factor α (TNF-α) and interleukin-1 (IL-1) in the suppressive activity of alveolar macrophages on autologous lung fibroblasts proliferation in sarcoidosis. We found that supernatants recovered from alveolar macrophages suppressed the proliferation of alveolar fibroblast in sarcoidosis by 35.5 ± 1.13% compared to 3 ± 16% in controls (p < 0.001 between the two groups). This suppression correlated with high content of TNF-α and IL-1 in sarcoidosis patients stage II-III (7.7 ± 2.9 ng/ml TNF-α and 157 ± 53 U/ml IL-1 compared to 3.4 ± 2.4 ng/ml TNF-α and 43 U/ml IL-1 in controls; p < 0.01 and p < 0.001, respectively). Both cytokines in sarcoidosis stage I were within the normal ranges. Exogenous TNF-α (1000-0.5 ng/ml) and IL-1 (500-0.24 ng/ml) had an additive suppressive activity on fibroblast proliferation which was partially reversed by indomethacin.